Expand Target Market in Business - Kurniati, P S; Razika, B (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to explain the extend target market of product by using a website. With the development of technology, it certainly has an impact on users of the website. This study used descriptive method with qualitative approach. It is to determine the efficiency of the information website. The result of this study is that technology has an important role inexpand the target market. Evidently, with information technology, every activity that is usually done manually can now be done anywhere without being limited by distance and time. The conclusions of this research are many advantages and benefits of accessing a website, many of them information that we need and can be easily obtained. With the use of the website, all requirements regarding information facilities are now very easy for users.